Quality of life of parents of Filipino children with special needs - Gomez, Ivan Neil B. (Education Quarterly, 2013)
Children with special needs (CWSN) experience disability in various areas. The birth of a child with special needs causes stress in the family, most especially among parents, consequently affecting parental quality of life (QOL).